Clothing Sales Promotion Activities: Social Media Marketing Aspects - Panya Tedsungnon (Journal La Bisecoman, 2020)
This article aims to increase clothes sales promotion activities on aspects of social media marketing. Marketing activities are aimed at making the product acceptable and then the product is liked by the market. With this sales promotion costs are generally lighter and the results achieved can be done in the short term. Clothing sales promotion using social media Facebook will be available with advertising facilities such as sponsored stories, CPC, Facebook page post ads, pages like Ads. Use status and tweet which is the simplest way of promotion. Instagram is this media used by teenagers who have smartphones. Use status and tweet which is the simplest way of promotion. Tendency of clothing sales promotions expect after buying, consumers will have the brand loyalty they bought